Hard particle powder for sintered bodies

JP7624358B2Active Publication Date: 2025-01-30DAIDO STEEL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021119670
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-20
Publication Date
2025-01-30
Estimated Expiration
2041-07-20

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、Coを含有しない合金粉末組成で、粉末特性や焼結特性を損なうことなく、焼結体における耐摩耗性を向上させることができる焼結体用硬質粒子粉末を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624358000006
    Figure 0007624358000006
  • Figure 0007624358000007
    Figure 0007624358000007
  • Figure 0007624358000008
    Figure 0007624358000008
Patent Text Reader

Abstract

To provide a hard particle powder for sintered bodies, having an alloy powder composition without including Co and capable of improving wear resistance in a sintered body without spoiling powder characteristics and sintering characteristics.SOLUTION: A hard particle powder for sintered bodies includes, by mass%, 0.01≤C≤1.0, 2.5≤Si≤3.3, 0.1≤Ni≤20.0, 5.0≤Cr≤15.0, 35.0≤Mo≤45.0 and the remainder consisting of Fe and inevitable impurities. A powder before sintering includes an alloy phase having a Laves phase C14 hexagonal crystal structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard particle powder for a sintered body, and more particularly to a hard particle powder for a sintered body which provides high wear resistance when produced into a sintered body (for example, an automobile engine valve seat). [Background technology]

[0002] MONICR7 is well known as a highly wear-resistant Co-based hard particle that forms a hard phase mainly composed of Mo silicide. Co-2Si-10Ni-25Cr-25Mo alloy powder, which is equivalent to MONICR7, is widely used in automobile engines under high load as a hard particle that contributes greatly to the wear resistance of automobile engine valve seats (hereinafter simply referred to as "valve seats"). For this reason, many prior arts have been proposed.

[0003] For example, Patent Document 1 listed below discloses a method for producing a wear-resistant sintered member in which a raw material powder containing a matrix-forming powder (iron, SUS316, SUS304, SUS310, SUS430) and a hard layer-forming powder (Co-28Mo-2.5Si-8Cr) is compacted and sintered for the purpose of dispersing a large amount of a hard layer in a matrix without impairing the wear resistance, strength, etc., in which 90 mass % or more of the matrix-forming powder is a fine powder with a maximum particle size of 46 μm and the proportion of the hard layer-forming powder in the raw material powder is 40 to 70 mass %.

[0004] In addition, in the following Patent Document 2, for the purpose of obtaining an iron-based sintered alloy material having excellent wear resistance, 0.2 to 3.0 parts by weight of solid lubricant powder (sulfide, fluoride) and / or 0.2 to 5.0 parts by weight of oxide stabilizer powder (Y, which is an oxide of a rare earth element) are added to 100 parts by weight of iron-based alloy powder consisting of pure iron powder, ferroalloy powder, carbon powder, fine carbide precipitated steel powder, and hard particle powder (Cr-Mo-Co system, Ni-Cr-Mo-Co system, etc.). 2 O 3 ,CeO 2 , CaTiO 3The present invention discloses a method for producing a wear-resistant iron-based alloy material for valve seats, which comprises compressing and molding an iron-based alloy powder containing added CrNbO2 and then sintering the powder to obtain a sintered body. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-107034 A [Patent Document 2] JP 2003-193173 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, the wear resistance required for valve seat materials has been further increased with the increase in engine load characteristics. The hard particle powders disclosed in the above Patent Documents 1 and 2 have excellent wear resistance required for valve seat materials, but contain a large amount of Co. Regarding Co, the resource price has risen sharply due to the recent increase in electric vehicles on a global scale and the sharp increase in demand for lithium-ion batteries, making it difficult to procure raw materials. In addition, if the Co concentration of the valve seat material is reduced, there is a risk that the required wear resistance, powder characteristics, and sintering characteristics will be impaired. For this reason, there has been a demand for development of a hard particle powder for sintered bodies that can achieve the wear resistance required for valve seat materials with an alloy composition that is easy to obtain raw materials and low cost.

[0007] In view of the above circumstances, an object of the present invention is to provide a hard particle powder for a sintered body, which has an alloy powder composition that does not contain Co, and which can improve the wear resistance of a sintered body without impairing the powder characteristics and sintering characteristics. [Means for solving the problem]

[0008] As a result of various investigations to solve the above problems, the inventors have discovered that if an alloy powder in which the area ratio of the Mo-Si hard phase (Laves phase C15 type face-centered cubic crystal structure) after sintering is increased from approximately 30% in conventional Co-based alloy powder to 60-85%, it is possible to obtain a sintered body with high hardness and excellent wear resistance even from Fe-based alloy powder, which tends to have low hardness and low wear resistance.

[0009] The present invention has been made based on the above findings, and the gist of the present invention is as follows. [1] In mass%, the composition is 0.01≦C≦1.0, 2.5≦Si≦3.3, 0.1≦Ni≦20.0, 5.0≦Cr≦15.0, 35.0≦Mo≦45.0, with the balance being Fe and unavoidable impurities; A hard particle powder for sintered bodies, characterized in that the powder before sintering contains an alloy phase of a Laves phase C14 type hexagonal crystal structure.

[0010] [2] The hard particle powder for sintered bodies according to [1], characterized in that the average circularity of each powder particle present within the average particle size range of D50±5 μm is 0.6 to 1.0.

[0011] [3] A hard particle powder for sintered bodies according to either [1] or [2], characterized in that after sintering, a Mo-Si hard phase having a Laves phase C15 type face-centered cubic crystal structure is present in an area ratio of 60 to 85%. Effect of the Invention

[0012] According to the present invention, it is possible to provide a hard particle powder for a sintered body, which has an alloy powder composition that does not contain Co, and which can improve the wear resistance of the sintered body without impairing the powder characteristics and sintering characteristics. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a cross-sectional view showing an outline of a valve seat wear tester. [Diagram 2] FIG. 4 is an explanatory diagram for explaining measurement points of the wear amount of the wear test piece. [Diagram 3] FIG. 2 is a diagram showing an X-ray diffraction data pattern of the hard particle powder before sintering according to Example 1. [Figure 4] FIG. 1 shows X-ray diffraction data patterns of sintered bodies, where (A) shows Example 1, (B) shows Comparative Example 1, and (C) shows Comparative Example 8. [Diagram 5] 1A is a scanning electron microscope photograph of the cross section of the hard particle powder after sintering, (A) is an example 1, (B) is a comparative example 1, and (C) is a comparative example 8. [Figure 6] FIG. 4 is a diagram showing the relationship between particle size and circularity for hard particle powder according to the embodiment. [Figure 7] 1A and 1B are scanning electron micrographs of the hard particle powders before sintering, where (A) shows Example 1 and (B) shows Example 26. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Next, a hard particle powder for sintered body according to one embodiment of the present invention (hereinafter, may be simply referred to as "hard particle powder") and a sintered body using this hard particle powder will be specifically described.

[0015] 1.Hard particle powder for sintered bodies The hard particle powder of this embodiment contains C, Si, Ni, Cr, and Mo, with the balance being Fe and unavoidable impurities.

[0016] (Reasons for limiting chemical components, etc.) The reasons for limiting the chemical components of the hard particle powder of this embodiment will be described in detail below. In the following description, "%" means "mass %" unless otherwise specified.

[0017] 0.01≦C≦1.0 C is an element that improves the hardness of the particle powder. C may be supplied from the graphite powder that constitutes the sintered body during sintering, but in industrial production, the lower limit is set to 0.01% in consideration of the amount of C that may be contained in the raw materials. However, excessive addition of C leads to deterioration of toughness due to the formation of carbides, so the upper limit is set to 1.0%. A more preferable range is 0.01≦C≦0.4.

[0018] 2.5≦Si≦3.3 Silicon is an element that is included to improve hardness by forming silicides. The reason why the lower limit of the amount of silicon is set to 2.5% is that if the amount of silicon is less than this, the area ratio of the Mo-Si alloy phase that forms a Laves phase C15 type crystal structure in the sintered alloy powder is low, and the powder hardness decreases. The reason why the upper limit of the amount of silicon is set to 3.3% is that if the amount of silicon is more than this, the area ratio of the Mo-Si alloy phase that forms a Laves phase C15 type crystal structure becomes too high, resulting in too high powder hardness, low sintering density, and large wear of the sintered body. A more preferable range is 2.7≦Si≦3.1.

[0019] 0.1≦Ni≦20.0 Ni is contained in an amount of 0.1% or more from the viewpoint of improving toughness. However, excessive addition of Ni leads to deterioration of wear resistance due to a decrease in heat resistance (melting point), so the upper limit is set to 20.0%. The preferred range is 5.0≦Ni≦11.0. The more preferred range is 7.0≦Ni≦10.0.

[0020] 5.0≦Cr≦15.0 Cr is an element that is included for the purpose of maintaining oxidation resistance and hardness. The reason why the lower limit of Cr is set at 5.0% is that if the content is below this level, the oxidation resistance and heat resistance decrease, and the wear resistance deteriorates. The reason why the upper limit of Cr is set at 15.0% is that if the content is above this level, the moldability decreases, the sintered density decreases, and the wear resistance deteriorates. The preferred range is 6.0≦Cr≦11.0. The more preferred range is 7.0≦Cr≦10.0.

[0021] 35.0≦Mo≦45.0 Mo is an element that is contained for the purpose of maintaining the hardness of the powder particles. The reason why the lower limit of the Mo content is set to 35.0% is that if the content is less than this, the area ratio of the Mo-Si alloy phase that forms the Laves phase C15 type crystal structure in the sintered alloy powder is low, and the powder hardness decreases. On the other hand, the reason why the upper limit of the Mo content is set to 45.0% is that if the content exceeds this, the area ratio of the Mo-Si alloy phase that forms the Laves phase C15 type crystal structure becomes too high, resulting in too high powder hardness, low sintering density, and large wear of the sintered body. The preferred range is 38.0≦Mo≦42.0. The more preferred range is 39.0≦Mo≦41.0.

[0022] In the hard particle powder for sintered body of this example, the balance other than the above-mentioned additive elements is Fe and inevitable impurities. Examples of impurity elements include oxygen (O), nitrogen (N), sulfur (S), phosphorus (P), copper (Cu), manganese (Mn), etc. The upper limits of each are O≦0.30, N≦0.10, S≦0.02, P≦0.03, Cu≦0.2, and Mn≦0.3.

[0023] (Method of manufacturing hard particle powder) The hard particle powder of this example can be produced by converting a molten alloy having a predetermined chemical composition into a powder form using an atomization method, etc. If necessary, a step of classifying the obtained alloy powder to adjust it to an appropriate particle size may be added.

[0024] In the above manufacturing method, the molten alloy can be obtained by weighing out each raw material so as to have a predetermined chemical composition, and melting the weighed raw materials using melting means such as an arc furnace, a high-frequency induction furnace, or a heating furnace.

[0025] Examples of methods for obtaining powder from a molten alloy include atomization (gas atomization, water atomization, etc.). When the gas atomization method is applied, N 2Gas such as Ar or He is sprayed at high pressure (for example, 1 to 10 MPa) to crush and cool the molten metal. The cooled molten metal approaches a spherical shape while falling freely in the spray chamber while remaining semi-molten, and hard particle powder is obtained. In order to improve the cooling effect, high-pressure water may be sprayed instead of gas.

[0026] The shape of hard particle powder also changes depending on the atomization conditions, etc. The shape of the powder affects the filling ability into a die and the density of the sintered body. The particle size (average particle size D50) of the hard particle powder is desirably within the range of 30 to 80 μm. Here, the average particle size D50 means a volume standard and can be measured using a laser diffraction / scattering type particle size distribution measuring device or the like.

[0027] In this embodiment, it is preferable to set the circularity of the hard particle powder to be within a predetermined range. Here, the circularity is defined as 4πS / L where S is the projected area of ​​the powder and L is the perimeter. 2 It is defined as follows. The circularity of a powder with a perfect circular shape is 1, and the more complicated the shape, the smaller the circularity becomes below 1. The present hard particle powder has high hardness and is difficult to deform, and if the powder is excessively irregular in shape, it becomes difficult to increase the density of the sintered body, so it is desirable to set the average circularity of each powder within the average particle size range of D50±5 μm to be within the range of 0.6 to 1.0.

[0028] In the hard particle powder for sintered body having a predetermined chemical composition obtained in this manner, an alloy phase having a hexagonal crystal structure of Laves phase C14 type containing a large amount of Mo and Si exists as a main phase.

[0029] 2. Sintered body The sintered body containing the hard particle powder of this embodiment can be manufactured through the mixing step, molding step, and sintering step described below. In the mixing step, the hard particle powder having the above-mentioned composition is mixed with the pure iron powder and the graphite powder to obtain a mixed powder. The blending amount of each component can be selected to be optimal depending on the purpose. If the amount of hard particle powder blended is too small, the wear resistance of the sintered body will decrease. Therefore, the amount of hard particle powder blended is preferably 5.0 mass% or more, and more preferably 10.0 mass% or more. On the other hand, if the amount of hard particle powder blended is excessive, the sintering characteristics will decrease. Therefore, the amount of hard particle powder blended is preferably 50.0 mass% or less, and more preferably 35.0 mass% or less.

[0030] Also, if the amount of graphite powder is too small, the wear resistance of the sintered body decreases. Therefore, the amount of graphite powder is preferably 0.5 mass% or more, and more preferably 0.8 mass% or more. On the other hand, if the amount of graphite powder is excessive, the sintering characteristics decrease. Therefore, the amount of graphite powder is preferably 2.0 mass% or less, and more preferably 1.5 mass% or less.

[0031] In the mixing step, materials other than the hard particle powder, the pure iron powder, and the graphite powder can be added as necessary, for example, a molding lubricant for improving moldability.

[0032] Next, in the compacting process, the mixed powder is compacted to obtain a green compact. The compacting conditions are not particularly limited, and the optimum conditions can be selected according to the purpose. In general, the higher the compacting pressure, the higher the green density. It is desirable to degrease the green compact obtained in the compacting process before sintering.

[0033] Next, in the sintering step, the green compact is sintered. It is preferable to select the optimum sintering conditions according to the composition of the green compact. In general, the higher the sintering temperature, the denser the sintered body can be obtained with a shorter heat treatment time. On the other hand, if the sintering temperature is too high, there is a problem that the hard particles diffuse too much into the iron-based matrix or melt. The optimum sintering conditions vary depending on the composition of the green compact, but it is usually preferable to sinter at 1100°C to 1300°C for 0.5 to 3 hours. Furthermore, it is preferable to perform the sintering in a reducing atmosphere (for example, in a decomposed ammonia atmosphere).

[0034] In the sintered body obtained through the sintering process, the Laves phase C14 type hexagonal crystal structure alloy phase that existed in the hard particle powder before sintering is transformed into a harder C15 type face-centered cubic crystal structure alloy phase (Mo-Si hardened phase). In the sintered body of this example, this Laves phase (C15 type face-centered cubic crystal structure) is present in an area ratio of 60 to 85% in the hard particle powder, which contributes to improving the wear resistance of the sintered body. EXAMPLES

[0035] Next, an embodiment of the present invention will be described. (Preparation of hard particle powder) The raw materials were weighed out so as to obtain the alloy compositions shown in Tables 1 and 2 below. Note that in each of the comparative examples shown in Table 2, at least one element falls outside the scope of the present invention. Comparative Example 01 has the composition of a conventional Co-based alloy powder (benchmark material) containing Co. The weighed raw materials were heated and melted in a high-frequency induction furnace to obtain molten alloys. Then, hard particle powders were obtained from the obtained molten alloys by atomization. Here, the hard particle powders were produced by water atomization in Examples 1 to 25 and Comparative Examples 1 to 9, and by gas atomization in Example 26.

[0036] [Table 1]

[0037] [Table 2]

[0038] (Characteristics evaluation of hard particle powder) The properties of the hard particle powders thus produced were evaluated. Specifically, the particle size distribution, apparent density, and flowability were evaluated in Examples 1 and 11 and Comparative Example 1. In addition, the hardness of the hard particle powders before and after sintering was evaluated for all Examples and Comparative Examples. Here, the particle size distribution was measured in accordance with the Japan Industrial Association standard: JIS Z 2510-2004. The apparent density was measured in accordance with the Japan Industrial Association standard: JIS Z 2504-2012, and the flowability was measured in accordance with the Japan Industrial Association standard: JIS Z 2502-2012. In addition, the hardness of the hard particle powder was measured using a microhardness tester. The hardness of the hard particle powder was measured using Vickers hardness with a load of 50 g. The measurement results for particle size distribution, apparent density and flowability are shown in Table 3, and the measurement results for hardness of the hard particle powder are shown in Tables 1 and 2.

[0039] [Table 3]

[0040] (Evaluation of hard particle powder shape) The shape (roundness) of the obtained hard particle powder was evaluated. Using a powder shape measuring device (CAMSIZER X-2 manufactured by Verder Scientific Co., Ltd.), the powder was sprayed in a dry state, dropped, photographed with a high-speed camera, and processed to measure the roundness of the powder. Figure 6 shows the measurement results (relationship between particle size and roundness) for Example 1 (produced by water atomization method) and Example 26 (produced by gas atomization method). Table 4 below shows the average particle size and circularity of the hard particle powders of Examples 1, 11, and 26 and Comparative Example 1. The circularity is shown as the average value of the circularity (11 points) for each powder that is within the range of the average particle size D50±5 μm.

[0041] [Table 4]

[0042] (Preparation of sintered body) Using the hard particle powders of Examples 1 to 26 and Comparative Examples 1 to 9, sintered bodies were produced in the following procedure. First, 69.2% by mass of pure iron powder (ASC100.29), 30% by mass of hard particle powder, and 0.8% by mass of graphite (CPB) were mixed together to obtain a raw material mixed powder for the sintered body. Next, the raw material mixed powders of Examples 1 to 26 and Comparative Examples 1 to 9 were compacted under a compaction pressure of 8 t / cm 2 The powder was compacted at 400°C for 1 hour to obtain a disk-shaped compact with a diameter of 35 mm and a thickness of 14 mm. The disk-shaped compact was then degreased in an air atmosphere at 400°C for 1 hour, and then decomposed in a decomposed ammonia atmosphere (N 2 +3H 2 ) for 1 hour to obtain a sintered body.

[0043] (Evaluation of sintering characteristics) The sintered density (density of the sintered body after sintering) of the produced sintered body was measured in accordance with the Japanese Industrial Association standard: JIS Z 2509-2004. The results are shown in Tables 1 and 2.

[0044] (Observation of the structure of sintered bodies and measurement of area ratio) The hard particle powder before sintering and the hard particle powder contained in the sintered body after sintering were subjected to structural observation by a scanning electron microscope (SEM) and analysis by X-ray diffraction. It was confirmed that the hard particle powder before sintering contained an alloy phase of a hexagonal crystal structure of Laves phase C14 type. As a representative example of the hard particle powder before sintering, the X-ray diffraction data pattern of the hard particle powder according to Example 1 is shown in FIG.

[0045] Next, it was confirmed that the hard particle powder contained in the sintered body after sintering contains a Mo-Si hard phase with a face-centered cubic crystal structure of Laves phase C15 type. As a representative example, X-ray diffraction data patterns of the sintered bodies according to Example 1, Comparative Example 1, and Comparative Example 8 are shown in FIG. Additionally, the area ratio of the Mo-Si hard phase in the hard particle powder was calculated from the SEM image of the powder cross section (see FIG. 5). In detail, the image processing software WinROOF was used to calculate the area ratio of the Mo-Si hard phase from the shade of color in the SEM image. The white parts in FIG. 5 are the Mo-Si hard phase. In each example in FIG. 5, it can be seen that the area ratio of the Mo-Si hard phase increases in the order of (B) Comparative Example 1 < (C) Comparative Example 8 < (A) Example 1. In the sintered bodies of each example and comparative example, the area ratio was calculated in three different fields of view, and the average value is shown in Tables 1 and 2 as the area ratio.

[0046] (Wear resistance test of sintered body) A wear resistance test of the sintered body (the prepared disk-shaped sintered body) was performed using a valve seat wear tester (hereinafter, simply referred to as the "wear tester") shown in Figure 1. First, the disk-shaped sintered body (diameter 35 mm x thickness 14 mm) was processed into a valve seat shape, which was used as each wear test piece. The wear test piece was then set in the wear tester by pressing it into a seat holder, and the wear tester was operated under the test conditions shown in Table 5 below, and the wear test piece was indirectly heated by gas flame heating of the valve, while the wear test piece was worn by a beating input caused by the crank drive.

[0047] [Table 5]

[0048] The amount of wear of the wear test piece was obtained by measuring the shape of the wear test piece before and after the wear test with a shape measuring device and calculating the difference D in the direction perpendicular to the surface of the wear test piece as shown in Figure 2 (an enlarged view of the part indicated by arrow A in Figure 1). The results are shown in Tables 1 and 2.

[0049] From the measurement results obtained as described above, the following can be seen. (About wear resistance) As shown in Table 1, the wear amount was less than 25 μm in all of Examples 1 to 26, but the wear amount was 25 μm or more in all of Comparative Examples 1 to 9. That is, the wear amounts in Examples 1 to 26 were smaller than those in Comparative Examples 1 to 9. Comparing Examples 1 to 26 with Comparative Examples 1 to 9, all of them satisfy the preferred conditions according to the present embodiment except for the component ranges. Therefore, it is found that the component compositions according to Examples 1 to 26 have the effect of improving the wear resistance of the sintered body (valve seat). From the viewpoint of crystal structure, the effect of improving the wear resistance of the sintered body (valve seat) is observed when the abundance ratio (area ratio) of the Laves phase C15 type (face-centered cubic crystal structure) alloy phase in the sintered hard particle powder is within the range of 60 to 85% as in Examples 1 to 26. On the other hand, as in Comparative Examples 1 to 9, it is found that the effect of improving the wear resistance is not obtained when the abundance ratio of the Laves phase C15 type alloy phase is less than 60% or exceeds 85%.

[0050] Looking closely at each of the comparative examples in Table 2, Comparative Example 1 is a conventional material. The wear amount is excellent at 25 μm, but since the Co content is high, it is susceptible to the cost impact of rising Co raw material prices, which is not preferable. The reason why the amount of wear in Comparative Example 2 was large is believed to be that the amount of C was too high, which resulted in too high hardness, poor moldability, and low sintered density.

[0051] The reason why the wear amount was large in Comparative Example 3 is believed to be that the amount of Si was small, so that the area ratio of the Laves phase C15 type alloy phase in the hard particle powder after sintering was low, and the powder hardness was reduced. The reason for the large wear amount in Comparative Example 4 is believed to be that the Si content was high, which resulted in a high area ratio of the Laves phase C15 type alloy phase in the sintered hard particle powder, resulting in high hardness, poor moldability, and low sintered density.

[0052] The increase in the amount of wear in Comparative Example 5 is believed to be due to the large amount of Ni, which resulted in a decrease in powder hardness. The increase in the amount of wear in Comparative Example 6 is believed to be due to the small amount of Cr, which resulted in a decrease in powder hardness. The reason why the wear amount was large in Comparative Example 7 is believed to be that the Cr content was too high, which resulted in too high hardness, poor moldability, and low sintered density.

[0053] The increase in the wear amount in Comparative Example 8 is believed to be due to the fact that the area ratio of the Laves phase C15 type alloy phase in the hard particle powder after sintering was low due to the small amount of Mo, resulting in a decrease in powder hardness. The wear amount in Comparative Example 9 was high because the amount of Mo was too high, which resulted in a high area ratio of the Laves phase C15 type alloy phase in the sintered hard particle powder, resulting in high hardness, poor moldability, and low sintered density.

[0054] (Characteristics other than wear resistance) Comparing the particle size distribution and powder characteristics shown in Table 3, it can be determined that the particle size distribution and powder characteristics of Example 1 and Example 11 do not impair the particle size distribution and powder characteristics of Comparative Example 1. The difference in particle size distribution is small, is due to variations during powder production, and does not impair the characteristics of Example 1 and Example 11. Furthermore, when comparing the sintered density as a sintering characteristic shown in Tables 1 and 2, the sintered density of each example is almost at the same level as the sintered density of Comparative Example 1, and no significant difference that would adversely affect the wear resistance was observed.

[0055] From the above, it was found that the hard particle powder of this embodiment, which is composed of a specified component system, can improve the wear resistance of a sintered body (valve seat) without substantially impairing the powder characteristics and sintering characteristics, and can obtain a sintered body with excellent wear resistance.

[0056] Although the present invention has been described in detail above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible within the scope of the present invention. For example, the above-mentioned examples were carried out assuming a valve seat, but the hard particle powder for sintered body of the present invention can also be used for mechanical structural parts other than valve seats.

Claims

1. In mass percent, 0.01≦C≦1.0 2.5≦Si≦3.3 0.1≦Ni≦20.0 5.0≦Cr≦15.0 35.0≦Mo≦45.0 The remainder is Fe and unavoidable impurities. A hard particle powder for sintered bodies, characterized in that the powder before sintering contains an alloy phase having a Laves phase C14 type hexagonal crystal structure.

2. 2. The hard particle powder for sintered bodies according to claim 1, characterized in that the average circularity of each powder particle present within the range of average particle size D50±5 μm is 0.6 to 1.

0.

3. 3. The hard particle powder for sintered bodies according to claim 1, characterized in that after sintering, a Mo-Si hard phase having a Laves phase C15 type face-centered cubic crystal structure is present in an area ratio of 60 to 85%.

Citation Information

Patent Citations

  • Iron-based abrasion-resistant alloy based on Laves phase strengthening and preparation method thereof

    CN103741049A

  • Abrasion resistant sintered member and manufacturing method therefor

    JP2003119542A

  • Method of producing wear resistant iron sintered alloy for valve seat

    JP2003193173A

  • Method for producing abrasion-resistant sintered member

    JP2007107034A

  • Wear-resistant sintered alloy and method for producing the same

    JP2010144237A